Analysis The Role of Peer Influence Towards Smoking Behavior Among Adolescent - Nur Inayah Ismaniar; Meliana Handayani; Sri Rahmayani (Pancasakti Journal Of Public Health Science And Research, 2025)
Smoking behavior among adolescents is a serious concern in public health efforts due to its long-term impact on health into adulthood. One of the main factors driving this behavior is peer influence, which plays a significant role in shaping habits and behavioral decisions, including smoking. At the Faculty of Sports and Health Sciences, Universitas Negeri Makassar, students who are expected to serve as role models for healthy behavior are frequently observed engaging in smoking activities, even within the campus environment. This phenomenon highlights the strong social influence within peer groups, making it essential to investigate the extent to which peer influence affects smoking behavior among students as an initial step in formulating effective interventions to create a smoke-free campus environment. The objective of this study was to analyze the role of peer influence on smoking behavior among students at the Faculty of Sports and Health Sciences, Universitas Negeri Makassar. This research employed a quantitative observational design with a cross-sectional approach. The study utilized a simple random sampling technique, given the homogeneous nature of the population, with a total sample size of 281 participants. The results indicated a significant relationship between peer influence and smoking behavior among FIKK UNM students. The analysis revealed that students with peers who smoke were more likely to smoke themselves. Future researchers are advised to explore other factors, such as the duration of smoking habits in relation to the length of friendships among adolescent smokers.